2011
DOI: 10.1074/jbc.r110.200329
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Role of Cdc42 in Regulating Mammalian Physiology

Abstract: Cdc42 is a member of the Rho GTPase family of intracellular molecular switches regulating multiple signaling pathways involved in actomyosin organization and cell proliferation. Knowledge of its signaling function in mammalian cells came mostly from studies using the dominant-negative or constitutively active mutant overexpression approach in the past 2 decades. Such an approach imposes a number of experimental limitations related to specificity, dosage, and/or clonal variability. Recent studies by conditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
130
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(137 citation statements)
references
References 86 publications
(89 reference statements)
3
130
1
3
Order By: Relevance
“…Those actions of Cdc42 that ensure the proper maintenance of epithelial structures served as a forecast of critically important functions for this GTPase in various developmental processes. Indeed, a number of studies using conditional knockout (CKO) mice have shown that the deletion of Cdc42 in epithelial stem/progenitor cells from a variety of tissues results in the disruption of intact epithelial structures, leading to severe and even lethal defects in embryonic organogenesis and tissue homeostasis (8,9). Defects in epithelial structure that accompany the deletion of Cdc42 have been suggested to affect cell fate determination, proliferation, survival, and differentiation during embryonic development (10 -14).…”
mentioning
confidence: 99%
“…Those actions of Cdc42 that ensure the proper maintenance of epithelial structures served as a forecast of critically important functions for this GTPase in various developmental processes. Indeed, a number of studies using conditional knockout (CKO) mice have shown that the deletion of Cdc42 in epithelial stem/progenitor cells from a variety of tissues results in the disruption of intact epithelial structures, leading to severe and even lethal defects in embryonic organogenesis and tissue homeostasis (8,9). Defects in epithelial structure that accompany the deletion of Cdc42 have been suggested to affect cell fate determination, proliferation, survival, and differentiation during embryonic development (10 -14).…”
mentioning
confidence: 99%
“…CDC42 is a member of the Rho GTPase family of intracellular molecular switches. It is responsible for regulating multiple signaling pathways and is involved in actomyosin organization and cell proliferation (30). Rho GTPase activity and expression are critical in the development and function of the kidney (31).…”
Section: Differential Expression Of Thousands Of Lncrnas In Iga-unassmentioning
confidence: 99%
“…Cdc42 é um membro da família das Rho GTPases, altamente conservado em diversas espécies (Melendez et al, 2011), conhecido principalmente por seu papel na organização do citoesqueleto, tráfico de vesículas, manutenção da polaridade celular (Cerione, 2004), orientação do citoesqueleto na divisão celular e manutenção da junções celulares (Qadir et al, 2015). Trabalhos recentes têm demonstrado também um possível papel na resposta ao dano no DNA.…”
Section: Discussionunclassified
“…Membro da família das Rho GTPases, Cdc42 foi inicialmente descoberto em S. cerevisiae como tendo envolvimento com a arquitetura do citoesqueleto de actina (Johnson and Pringle, 1990). O gene homólogo em humanos é altamente conservado, sugerindo que essa GTPase pode desempenhar importantes papéis na biologia de células de mamíferos (Melendez et al, 2011). A importância de Cdc42 fica evidente quando se estuda camundongos nocaute para esse gene.…”
Section: Cell Division Cycle 42 (Cdc42)unclassified
See 1 more Smart Citation